2014
DOI: 10.1111/ijd.12425
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of stage Ia and Ib mycosis fungoides with psoralen UVA monotherapy: an observational study in tertiary hospitals in the Canary Islands

Abstract: Psoralen with UVA is a safe and effective treatment for early-stage MF. Patch disease responds more favorably than plaque disease and is associated with a longer period of DFS. Maintenance treatment does not appear to reduce recurrence. Current evidence suggests that the proposed revision to the classification of MF, which takes into account the extent and type of disease, more accurately predicts response to PUVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Unfortunately, PUVA is linked with increased incidence of non‐melanoma skin cancers in psoriatic patients in a dose‐dependent manner, especially when cumulative dose reaches 2000 J or over 200 applications have been performed . Moreover, as we recently evaluated in a Critical Appraisal Topic, only three single centre studies published in literature have directly compared relapse rates and RFI between patients who received maintenance phase and those who underwent follow‐up. None of these studies has shown a significant difference in both RR and RFI, and more important, the evidence is based only on small cohorts without randomization.…”
Section: Towards a Shared Standardized Schedule For Puva And Nb‐uvb mentioning
confidence: 99%
“…Unfortunately, PUVA is linked with increased incidence of non‐melanoma skin cancers in psoriatic patients in a dose‐dependent manner, especially when cumulative dose reaches 2000 J or over 200 applications have been performed . Moreover, as we recently evaluated in a Critical Appraisal Topic, only three single centre studies published in literature have directly compared relapse rates and RFI between patients who received maintenance phase and those who underwent follow‐up. None of these studies has shown a significant difference in both RR and RFI, and more important, the evidence is based only on small cohorts without randomization.…”
Section: Towards a Shared Standardized Schedule For Puva And Nb‐uvb mentioning
confidence: 99%
“…Taking into account all data analysed in this CAT, we conclude that there is inadequate evidence to support the routine introduction of a maintenance phase in the PUVA treatment regimen for early‐stage MF. In fact, in all three relevant studies, although nonrandomized and controlled, there was no evidence of a benefit from a maintenance regimen both in terms of relapse reduction and RFI or disease‐free survival in comparison with simple follow‐up . The results from the studies do not allow us to evaluate if very prolonged maintenance schedules may effectively prolong RFI, as has been proposed in a retrospective study .…”
Section: Discussionmentioning
confidence: 92%
“…Lastly, we excluded all studies without a direct comparison between patients who underwent maintenance regimens after CR and those who received no further therapies (5). At the end of this accurate analysis, three works were selected for critical appraisal . We did not find any new relevant articles by a manual search of related articles.…”
Section: Critical Appraisalmentioning
confidence: 99%
See 2 more Smart Citations